Bawal Bastos App: Using Mobile and Web Technology for Handling Reports of Gender-Based Sexual Harassment in Public Spaces - Ching, Gladys Mavilyn Agnasan; Villarica, Mia Villar (International Journal of Computing Sciences Research; Vol 9 (2025): Volume 9, 2025)
Purpose – This study aims to develop a two-way information technology system consisting of a mobile application (BLB App) and a web application (BLB Admin Portal) for filing and handling case reports on gender-based sexual harassment (GBSH) in public spaces of Los Baños, Laguna, Philippines. Establishment review and emergency features such as location-based messaging and press-to-call barangay hotline directory were also implemented. Method – The study employed descriptive and developmental research methodologies, incorporating the Safe Spaces Act of the Philippines during the conceptualization phase. The software development process adhered to the Scrum Agile methodology. Results – The acceptability evaluation demonstrates that both the mobile and web applications meet all criteria across the indicators. The BLB App’s geolocation accuracy, evaluated in various locations in Los Baños, Laguna, revealed statistically satisfactory results. Conclusion – The BLB mobile application facilitates comprehensive case reporting, capturing incident details such as location, time, victim information, incident details, and evidence upload. The BLB admin portal streamlines case report management, including case closure, routing cases to the appropriate channels, and data analysis, which features heatmap generation based on case data. Recommendations – Several recommendations were identified such as improving accessibility of emergency features through widgets or gesture recognition; enhancing the Safe Spaces Act information page; strengthening data security with encryption for personal identifiable information; and expanding the scope of case reporting to include Violations Against Women and their Children. Research Implications – While the study focuses on a specific locality, the application could be adopted by other local government units due to its alignment with national policy. It also emphasizes the need for further investigation into geolocation enhancements both locally and nationally and suggests that establishment review data could provide valuable insights for a more comprehensive analysis.